Use of a Prescription Drug-Monitoring Program by Emergency and Surgical Prescribers: Results of a Hospital Survey. Issue 1 (February 2019) - Leas, Daniel; Seymour, Rachel B.; Wally, Meghan K.; Hsu, Joseph R.; Beuhler, Michael; Bosse, Michael J.; Gibbs, Michael; Griggs, Christopher; Jarrett, Steven; Runyon, Michael; Saha, Animita; et al.
Background: Drug overdoses are the leading cause of death due to injury in the USA. Currently, 49 states have prescription drug-monitoring programs (PDMPs) available to prescribers. Questions/Purposes: We aimed to assess knowledge and practice of two groups of acute-care prescribers regarding controlled substances. Methods: A 16-question survey was distributed to a list of surgical and emergency medicine prescribers at our institution. The survey asked about prescriber demographics, previous experiences with a PDMP, and opinions about patient risk factors available within an electronic medical record (EMR). Results: We received 60 responses (27.1% response rate). All prescribers recognized a growing problem with opioids, both in general and in their own practices, with an average rating of 8.3/10 and 7.9/10, respectively. Although 95% were aware a PDMP was available, only 60% were registered users. Emergency medicine prescribers were significantly more likely to have registered and used the database; 52% said the PDMP was too time-consuming and 23% said the information was not easy to use. All respondents who reported PDMP use indicated it carried some clinical utility, with 87% reporting it to be "somewhat" or "very" useful. Emergency medicine prescribers were more likely to use the PDMP regularly, with 73% selecting "somewhat frequently" or higher, while only 9% of surgery prescribers indicated the same. Of all respondents, 97% agreed that an integrated alert in the existing EMR would be helpful. Conclusion: Acute-care prescribers at our institution are universally aware of the opioid epidemic, but efficient and useful tools for identifying at-risk patients are lacking. Our prescribers desired an alert system integrated into the EMR to highlight targeted risk factors.